Ecological genomics: making the leap from model systems in the lab to native populations in the field. Issue 1 (1st February 2007) - Travers, Steven E.; Smith, Melinda D.; Bai, Jianfa; Hulbert, Scot H.; Leach, Jan E.; Schnable, Patrick S.; Knapp, Alan K.; Milliken, George A.; Fay, Philip A.; Saleh, Amgad; Garrett, Karen A.
Abstract : Recent reviews have emphasized the need to incorporate genomics into ecological field studies to further understand how species respond to changing environmental conditions. Genomic tools, such as cDNA (complementary DNA) microarrays, allow for the simultaneous analysis of gene expression of thousands of genes from all or part of an organism's genome (the transcription profile), thereby revealing the genetic mechanisms that underlie species' responses to environmental change. However, despite their potential, two major limitations have hindered the incorporation of microarrays and other genomic tools into field studies: (1) the limited availability of microarrays for ecologically relevant, non‐model species and limited financial resources for developing new microarrays; and (2) concern that high sensitivity of gene expression to even subtle alterations in environmental conditions will hinder detection of relevant changes in field measures of transcription profiles. Here, we show that with cross‐species hybridizations of microarrays developed for a closely related model organism, an appropriate experimental design, and sufficient replication, transcriptional profiling can successfully be incorporated into field studies. In this way, relevant changes in gene expression with changing environmental conditions can be detected.